Thermo-mechanical extrusion pretreatment for conversion of soybean hulls to fermentable sugars - Yoo, Juhyun; Alavi, Sajid; Vadlani, Praveen V.; Amanor-Boadu, Vincent (My University, 2012)
Thermo-mechanical extrusion pretreatment for lignocellulosic biomass was investigated using soybean hulls as the substrate. The enzyme cocktail used to hydrolyze pretreated soybean hulls to fermentable sugars was optimized using response surface methodology (RSM). Structural changes in substrate and sugar yields from thermo-mechanical processing were compared with two traditional pretreatment methods that utilized dilute acid (1% sulfuric acid) and alkali (1% sodium hydroxide). Extrusion processing parameters (barrel temperature, in-barrel moisture, screw speed) and processing aids (starch, ethylene glycol) were studied with respect to reducing sugar and glucose yields. The conditions resulting in the highest cellulose to glucose conversion (95%) were screw speed 350 rpm, maximum barrel temperature 80 C and in-barrel moisture content 40% wb. Compared with untreated soybean hulls, glucose yield from enzymatic hydrolysis of soybean hulls increased by 69.6%, 128.7% and 132.2%, respectively, when pretreated with dilute acid, alkali and extrusion.
Keywords: Soybean hulls; Lignocellulosic; Ethanol; Pretreatment; Extrusion